Development and application of a novel recombinant Aleuria aurantia lectin with enhanced core fucose binding for identification of glycoprotein biomarkers of hepatocellular carcinoma. Issue 24 (28th November 2016) - Norton, Pamela; Comunale, Mary Ann; Herrera, Harmin; Wang, Mengjun; Houser, Josef; Wimmerova, Michaela; Romano, Patrick R.; Mehta, Anand
Abstract : The Aleuria aurantia lectin (AAL) derived from orange peel fungus contains five fucose‐binding sites that recognizes fucose bound in α‐1, 2, α‐1, 3, α‐1, 4, and α‐1, 6 linkages to N ‐acetylglucosamine and galactose. Recently, we have created several recombinant AAL (rAAL) proteins that had altered binding affinity to fucose linkages. In this report, we further characterize the binding specificity of one of the mutated lectins, N224Q lectin. This lectin was characterized by lectin Western blotting, surface plasmon resonance, and glycan microarray and shown to have increased binding to fucosylated glycan. Subsequently, we used this lectin to identify secreted fucosylated glycoproteins from a fetal hepatic cell line. Proteomic analysis revealed several glycoproteins secreted by the fetal cell line that were bound by N224Q lectin. These findings were confirmed by subsequent proteomic analysis of human serum from control patients or patients with hepatocellular carcinoma. These represent candidate oncofetal markers for liver cancer.